Functional communication training and noncontingent reinforcement in treatment of stereotypy. (19th December 2017) - Boyle, Megan A.; Ortman, Mary E.; Beckman, Alexandra C.; Aholt, Stephanie L.; Keenan, Ginny L.
Abstract : A 6‐year‐old boy with autism spectrum disorder engaged in automatically maintained stereotypy in the form of opening and closing doors. A functional analysis confirmed that he also emitted problem behavior that was maintained by access to stereotypy. We evaluated the separate and combined effects of functional communication training and arbitrary noncontingent reinforcement on both response classes. Results showed that the combination of functional communication training and noncontingent reinforcement was more effective at reducing stereotypy than either intervention on its own, although effects on problem behavior were unclear. These results suggest that combinations of interventions may be useful in the treatment of automatically maintained problem behavior.